A polyvinyl alcohol microsphere-based injectable filling hydrogel and a preparation method thereof
Patent Information
- Application Number
- CN202611434802.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-16
- Publication Date
- 2026-10-20
AI Technical Summary
[0005]鉴于背景技术中存在的技术问题,本申请提供了一种基于聚乙烯醇微球的注射填充水凝胶的制备方法,通过在聚乙烯醇上接枝甲基丙烯酸缩水甘油酯,合成甲基丙烯酸化聚乙烯醇后制成微球,与在酸性条件下接枝3-氨基苯硼酸制成的改性透明质酸复合,得到注射填充水凝胶,具有剪切变稀和自愈合特性,注射后原位自愈合形成的整体性凝胶网络可保证植入部位长期稳定的占位与三维形态的维持,同时,该网络作为仿生支架,可引导宿主细胞迁移、增殖及胶原蛋白的分泌,积极促进组织整合再生,解决了微球作为惰性填料导致的注射堵塞、微球易位以及现有微球复合凝胶难以诱导组织再生的缺陷
1、在本申请的技术方案中,通过在聚乙烯醇上接枝甲基丙烯酸缩水甘油酯得到甲基丙烯酸化聚乙烯醇,冻干制成微球后,与接枝3-氨基苯硼酸的冻干改性透明质酸复合,制备得到注射填充水凝胶,该注射填充水凝胶以含反应性基团的聚乙烯醇微球作为活性交联节点,与含互补基团的基质高分子之间形成动态可逆共价键,从根本上消除微球-基质弱界面,赋予体系剪切变稀和自愈合特性,可实现顺畅注射,注射后原位自愈合形成的整体性凝胶网络,可保证植入部位长期稳定的占位与三维形态维持,避免因体位变动、肌肉运动等生理应力导致的结构塌陷或微球分散。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This application relates to the field of hydrogel materials technology, specifically to an injection-filled hydrogel based on polyvinyl alcohol microspheres and its preparation method. Background Technology
[0002] Injectable hydrogels are a type of polymeric material that is a flowable liquid precursor under normal temperature or physiological conditions. They can be injected into the body through syringes, microneedles, or catheters via minimally invasive methods. They rely on temperature, pH, ions, light, chemical reactions, and intermolecular forces to trigger an in-situ sol-gel phase transition, directly forming a three-dimensional hydrophilic network hydrogel scaffold at the lesion site.
[0003] In the field of injectable fillers, various microsphere composite gel systems have been developed. Polyester microspheres, such as polylactic acid and polycaprolactone, are often combined with cross-linked sodium hyaluronate gel to improve filling durability. However, polylactic acid microspheres are easily hydrolyzed and degraded in aqueous environments, affecting long-term stability and resulting in unsatisfactory long-term performance. Polycaprolactone microspheres, on the other hand, have high crystallinity and strong hydrophobicity, with a complete in vivo degradation cycle of 3-5 years. Although hyaluronic acid-based gels have excellent immediate filling effects and biocompatibility, they generally suffer from short in vivo retention time and insufficient mechanical properties.
[0004] Polyvinyl alcohol (PVA) is a biocompatible polymer. Current techniques typically involve uniformly dispersing drug-loaded PVA microspheres in a chitosan / β-glycerophosphate sodium thermosensitive hydrogel precursor solution, utilizing body temperature to induce a sol-gel transition and embedding the microspheres within the gel network. However, the PVA microspheres are merely physically encapsulated; there is a lack of covalent bonds or high-affinity physical cross-links between the microsphere surface and the gel matrix. Under injection shear flow, microspheres are prone to phase separation from the polymer chains, leading to localized enrichment and aggregation of microspheres at the needle tip, causing needle blockage. After injection, the low cross-linking density and modulus of the external physical gel itself cannot effectively constrain the migration and release of microspheres in vivo. Simultaneously, the modulus mismatch between the microspheres and the matrix induces interfacial debonding and crack propagation, ultimately resulting in gel structure disintegration, uncontrolled drug release, and loss of occupancy function. Summary of the Invention
[0005] In view of the technical problems existing in the background art, this application provides a method for preparing an injection-filling hydrogel based on polyvinyl alcohol microspheres. By grafting glycidyl methacrylate onto polyvinyl alcohol to synthesize methacrylated polyvinyl alcohol, microspheres are made. These microspheres are then combined with modified hyaluronic acid prepared by grafting 3-aminophenylboronic acid under acidic conditions to obtain an injection-filling hydrogel. This hydrogel has shear-thinning and self-healing properties. The integral gel network formed by in-situ self-healing after injection can ensure long-term stable occupancy and maintenance of three-dimensional morphology at the implantation site. At the same time, this network, as a biomimetic scaffold, can guide the migration, proliferation, and collagen secretion of host cells, actively promoting tissue integration and regeneration. This solves the defects of microspheres as inert fillers, such as injection blockage and microsphere displacement, as well as the difficulty of inducing tissue regeneration in existing microsphere composite gels.
[0006] To achieve the above objectives, in a first aspect, embodiments of this application provide a method for preparing an injection-filled hydrogel based on polyvinyl alcohol microspheres, comprising the following steps: Polyvinyl alcohol is dissolved in a solvent to obtain a first reaction solution. p-Dimethylaminopyridine is added to the first reaction solution and dissolved to obtain a second reaction solution. Glycidyl methacrylate is mixed with the solvent and then added to the second reaction solution to carry out a first grafting reaction. After the reaction is completed, polyvinyl methacrylate is obtained by precipitation, washing and drying. Sodium hyaluronate was dissolved in an acidic solution, and then N-hydroxysuccinimide, 1-ethyl-(3-dimethylaminopropyl)carbodiimide salt, and 3-aminophenylboronic acid were added sequentially to carry out a second grafting reaction. After the reaction was completed, modified hyaluronic acid was obtained by dialysis and lyophilization. The methacrylated polyvinyl alcohol was made into methacrylated polyvinyl alcohol microspheres, and the methacrylated polyvinyl alcohol microspheres were combined with the modified hyaluronic acid to obtain an injection-filled hydrogel.
[0007] Further, the step of preparing the methacrylated polyvinyl alcohol into methacrylated polyvinyl alcohol microspheres includes: The methacrylated polyvinyl alcohol was prepared into a solution with a mass-volume fraction of 4%~7.5% w / v. The solution was then used to prepare microspheres by microfluidic technology. After fixation, washing, and freeze-drying, the methacrylated polyvinyl alcohol microspheres were obtained. The flow rate ratio of the aqueous phase to the oil phase in the microfluidic method was 1:(3~7.5). The step of combining the methacrylated polyvinyl alcohol microspheres with the modified hyaluronic acid includes: After incubating the methacrylated polyvinyl alcohol microspheres in water, the modified hyaluronic acid was added to dissolve them and a gel was obtained. After standing, aspirating into a syringe, and refrigerating, an injection-filled hydrogel was obtained. The particle size of the methacrylated polyvinyl alcohol microspheres after incubation in water is 140~220μm.
[0008] In some embodiments, methacrylated polyvinyl alcohol is prepared into a solution with a mass-volume fraction of 4% to 7.5% w / v, and then the solution is used to prepare microspheres by microfluidic method. The flow rate ratio of the aqueous phase to the oil phase in the microfluidic method is 1:(4~5). After fixation by ultraviolet light irradiation, washing with carbon tetrachloride and water, and freeze drying, methacrylated polyvinyl alcohol microspheres are obtained.
[0009] Further, the molar ratio of polyvinyl alcohol, p-dimethylaminopyridine, and glycidyl methacrylate is (100~150):1:(2.9~3.9); the reaction temperature of the first grafting reaction is 50~70℃, and the reaction time is 5~8h.
[0010] In some embodiments, the molar ratio of polyvinyl alcohol, p-dimethylaminopyridine, and glycidyl methacrylate is (100~150):1:(3~3.1), the reaction temperature of the first grafting reaction is 60°C, and the reaction time is 6h.
[0011] Further, the solvent is dimethyl sulfoxide; when the polyvinyl alcohol is dissolved in the solvent, the feed ratio of the polyvinyl alcohol to the dimethyl sulfoxide is (4~6) g: (80~100) mL; when the glycidyl methacrylate is mixed with the solvent, the feed ratio of the glycidyl methacrylate to the dimethyl sulfoxide is (0.3~0.5) g: (8~12) mL.
[0012] In some embodiments, 5 g of polyvinyl alcohol is dissolved in 90 mL of dimethyl sulfoxide; and 0.39 g of glycidyl methacrylate is dissolved in 10 mL of dimethyl sulfoxide.
[0013] Further, the ratio of sodium hyaluronate to the acidic solution is (1~2) g : (100~200 mL); the pH of the acidic solution is 4.7~4.8.
[0014] In some embodiments, 1.5 g of sodium hyaluronate is dissolved in 150 mL of an acidic solution with a pH of 4.7 to 4.8.
[0015] Further, the molar ratio of N-hydroxysuccinimide, 1-ethyl-(3-dimethylaminopropyl)carbodiimide salt, and 3-aminophenylboronic acid is (4~5):(3.5~4.5):(4~5).
[0016] In some embodiments, the molar ratio of N-hydroxysuccinimide, 1-ethyl-(3-dimethylaminopropyl)carbodiimide salt, and 3-aminophenylboronic acid is 4.5:4:4.5.
[0017] Furthermore, the reaction temperature of the second grafting reaction is 25~35℃, the reaction time is 20~28h, and the dialysis time is 60~84h.
[0018] In some embodiments, the reaction temperature of the second grafting reaction is 30°C, the reaction time is 22-26 h, and the dialysis time is 70-74 h.
[0019] Furthermore, the mass ratio of the methacrylated polyvinyl alcohol microspheres to the modified hyaluronic acid is 1:(3.3~5).
[0020] In some embodiments, the mass ratio of methacrylated polyvinyl alcohol microspheres to modified hyaluronic acid is 1:3.75.
[0021] Furthermore, the methacrylated polyvinyl alcohol microspheres are incubated in water for 10-14 hours, the settling time is 6 hours, and the settling temperature is 4°C.
[0022] Secondly, embodiments of this application provide an injection-filled hydrogel based on polyvinyl alcohol microspheres, which is prepared by the preparation method of the injection-filled hydrogel based on polyvinyl alcohol microspheres described in the first aspect.
[0023] The beneficial technical effects of this application are as follows: 1. In the technical solution of this application, methacrylated polyvinyl alcohol is obtained by grafting glycidyl methacrylate onto polyvinyl alcohol, which is then freeze-dried into microspheres. These microspheres are then combined with freeze-dried modified hyaluronic acid grafted with 3-aminophenylboronic acid to prepare an injection-filling hydrogel. This injection-filling hydrogel uses polyvinyl alcohol microspheres containing reactive groups as active cross-linking nodes to form dynamic reversible covalent bonds with matrix polymers containing complementary groups. This fundamentally eliminates the weak interface between the microspheres and the matrix, endowing the system with shear thinning and self-healing properties. This enables smooth injection, and the integral gel network formed by in-situ self-healing after injection can ensure long-term stable occupancy and three-dimensional morphology maintenance at the implantation site, avoiding structural collapse or microsphere dispersion caused by physiological stress such as body position changes and muscle movement.
[0024] 2. In the technical solution of this application, the gel network structure formed by in-situ self-healing after injection of the hydrogel can promote host cell migration, proliferation, and collagen secretion, actively promoting tissue regeneration. This overcomes the clinical limitations of traditional microsphere fillers, which are prone to displacement and aggregation to form nodules; hyaluronic acid fillers, which have rapid decline in mechanical support and short maintenance time; and existing microsphere composite gels, which are difficult to induce regeneration due to interfacial deadhesion and structural disintegration. While achieving stable in vivo placement, it also has advantages such as simplified preparation process and product application safety, providing an injectable filler hydrogel material that integrates long-term morphological support and active tissue regeneration function for tissue filling and repair, medical aesthetics, and local drug sustained release.
[0025] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Attached Figure Description
[0026] To more clearly illustrate the technical solutions of this application, the accompanying drawings used in this application will be briefly described below. Obviously, the drawings described below are merely some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without any creative effort.
[0027] Figure 1 This is a schematic diagram of the synthetic route for methacrylated polyvinyl alcohol and modified hyaluronic acid in this application; Figure 2 This is a microstructure test image of the methacrylated polyvinyl alcohol microspheres prepared in Example 1 of this application; Figure 3 This is a statistical chart showing the size of the methacrylated polyvinyl alcohol microspheres prepared in Example 1 of this application after incubation. Figure 4 The above are the 1H NMR spectra of sodium hyaluronate and modified hyaluronic acid in Example 1 of this application. Figure 5 This is a rheological property test diagram of the injection-filled hydrogel prepared in Example 1 of this application; Figure 6 This is a test image of the self-healing performance of the injection-filled hydrogel prepared in Example 1 of this application; Figure 7 This is an in vitro injection extrusion force test diagram of the injection-filled hydrogel prepared in Example 1 of this application; Figure 8 This image shows the in vitro cell biocompatibility test results of the methacrylated polyvinyl alcohol microspheres and the injection-filled hydrogel prepared in Example 1 of this application. Figure 9 Hematoxylin-eosin staining image of the injectable filler hydrogel prepared in Example 1 of this application for subcutaneous implantation tissue reaction test; Figure 10 Masson staining image of the subcutaneous implantation tissue reaction test of the injectable filling hydrogel prepared in Example 1 of this application; Figure 11 Sirius red staining image of the subcutaneous implantation tissue reaction test of the injectable filling hydrogel prepared in Example 1 of this application. Detailed Implementation
[0028] The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application and are therefore merely examples, and should not be used to limit the scope of protection of this application.
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.
[0030] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0031] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0032] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0033] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0034] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0035] Unless otherwise specified, the terms "comprising" and "including" as used in this application are open-ended. For example, "comprising" and "including" may mean that other components not listed may also be included or contained.
[0036] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.
[0037] The embodiments of this application will be described in further detail below with reference to the accompanying drawings and examples. The detailed description of the following embodiments and the accompanying drawings are used to illustrate the principles of this application by way of example, but should not be used to limit the scope of this application, that is, this application is not limited to the described embodiments.
[0038] To address the technical problems of injection blockage, microsphere displacement, and the difficulty of inducing tissue regeneration in existing microsphere composite gels caused by microspheres as inert fillers, this application provides, in a first aspect, a method for preparing an injection-filled hydrogel based on polyvinyl alcohol microspheres, comprising the following steps: Polyvinyl alcohol was dissolved in a solvent to obtain a first reaction solution. p-Dimethylaminopyridine was added to the first reaction solution and dissolved to obtain a second reaction solution. Glycidyl methacrylate was mixed with a solvent and then added to the second reaction solution to carry out the first grafting reaction. After the reaction was completed, polyvinyl methacrylate was obtained by precipitation, washing and drying. Sodium hyaluronate was dissolved in an acidic solution, and then N-hydroxysuccinimide, 1-ethyl-(3-dimethylaminopropyl)carbodiimide salt, and 3-aminophenylboronic acid were added sequentially to carry out a second grafting reaction. After the reaction was completed, modified hyaluronic acid was obtained by dialysis and lyophilization. Methacrylated polyvinyl alcohol was made into methacrylated polyvinyl alcohol microspheres, and then the methacrylated polyvinyl alcohol microspheres were combined with modified hyaluronic acid to obtain an injection-filled hydrogel.
[0039] In the technical solution of this application, a hydrogel is prepared by combining methacrylated polyvinyl alcohol grafted with glycidyl methacrylate and modified hyaluronic acid grafted with 3-aminophenylboronic acid. Dynamic reversible covalent bonds are formed between polyvinyl alcohol microspheres containing reactive groups and matrix polymers containing complementary groups. The system has shear-thinning and self-healing properties, enabling smooth injection and maintaining a three-dimensional gel network structure. At the same time, this network acts as a biomimetic scaffold, which can guide the migration, proliferation and collagen secretion of host cells, and actively promote tissue integration and regeneration.
[0040] In some embodiments, polyvinyl methacrylate (PVA) is prepared into a solution with a mass-volume fraction of 4% to 7.5% w / v. The solution is then used to prepare microspheres via microfluidic technology. After fixation, washing, and freeze-drying, PVA microspheres are obtained. The flow rate ratio of the aqueous phase to the oil phase in the microfluidic method is 1:(3~7.5). The step of compounding the PVA microspheres with modified hyaluronic acid includes: incubating the PVA microspheres in water, adding modified hyaluronic acid to dissolve them to obtain a gel, and then allowing it to stand, drawing it into a syringe, and refrigerating it to obtain an injection-filled hydrogel. The particle size of the PVA microspheres after incubation in water is 140~220 μm.
[0041] In this embodiment, methacrylated polyvinyl alcohol is used as the raw material for microspheres. Methacrylic acid provides photocrosslinking properties, and the microspheres can be cured by light after formation. Modified hyaluronic acid serves as the matrix of the composite hydrogel, providing certain mechanical strength and self-healing properties while restricting microsphere migration.
[0042] In one specific embodiment, methacrylated polyvinyl alcohol was prepared into a solution with a mass-volume fraction of 5% w / v and then microspheres were fabricated by microfluidic method. The flow rate ratio of the aqueous phase to the oil phase in the microfluidic method was 7:30. After fixation by ultraviolet light irradiation, washing with carbon tetrachloride and water, and freeze-drying, methacrylated polyvinyl alcohol microspheres were obtained.
[0043] This setup, employing a microfluidic method to form a water-in-oil structure, with the oil phase serving as the continuous phase to provide controllable shear force, results in methacrylated polyvinyl alcohol microspheres exhibiting good monodispersity, strong batch reproducibility, high bioactivity retention, and controllable aseptic properties. Ultraviolet light irradiation further accelerates the crosslinking rate of the microspheres, improves the stability of the crosslinked structure, and enhances biocompatibility. Carbon tetrachloride washing displaces internal moisture from the microspheres, reducing surface tension and inhibiting aggregation. Water washing removes residual carbon tetrachloride and water-soluble impurities, ensuring biocompatibility.
[0044] In some embodiments, the molar ratio of polyvinyl alcohol, p-dimethylaminopyridine, and glycidyl methacrylate is (100~150):1:(2.9~3.9); the reaction temperature of the first grafting reaction is 50~70℃, and the reaction time is 5~8h.
[0045] It should be noted that the molar amount of polyvinyl alcohol is calculated based on the repeating units of ethylene alcohol.
[0046] It can be explained that after the glycidyl methacrylate is mixed with the solvent, the second reaction solution is added, and after 20-40 minutes, the temperature is raised to 50-70℃ to carry out the first grafting reaction.
[0047] In this embodiment, a low-temperature, slow pre-grafting process is first performed to prevent excessive local cross-linking and explosive polymerization. Then, the temperature is increased to carry out the first grafting reaction, which makes the grafting rate more controllable and the product more stable.
[0048] More preferably, in some specific embodiments, the molar ratio of polyvinyl alcohol, p-dimethylaminopyridine, and glycidyl methacrylate is (100~150):1:(3~3.1), and the reaction temperature for the first grafting reaction is 60°C and the reaction time is 6 hours after adding the second reaction solution for 30 minutes.
[0049] With this setup, using the amount of catalyst p-dimethylaminopyridine as equivalent 1, the molar ratio is easier to control, and the experiment has better repeatability. When the temperature is not increased for 30 minutes, the system first undergoes a slow and weakly exothermic pre-grafting, during which the heat is slowly dissipated. Then, when the temperature is increased to 60°C, the steady-state and controllable grafting reaction can be initiated.
[0050] In some embodiments, the solvent is dimethyl sulfoxide; when polyvinyl alcohol is dissolved in the solvent, the feed ratio of polyvinyl alcohol to dimethyl sulfoxide is (4~6) g: (80~100) mL; when glycidyl methacrylate is mixed with the solvent, the feed ratio of glycidyl methacrylate to dimethyl sulfoxide is (0.3~0.5) g: (8~12) mL.
[0051] In this embodiment, dimethyl sulfoxide (DMSO) is used as a polar aprotic organic solvent, which can efficiently dissolve polyvinyl alcohol, p-dimethylaminopyridine, and glycidyl methacrylate. DMSO has a boiling point of 189°C at atmospheric pressure, which is much lower than the grafting reaction temperature of the system. It is not easily volatilized when heated, and the system concentration is more stable.
[0052] In one specific embodiment, the feeding ratio of polyvinyl alcohol to dimethyl sulfoxide is 5g:90mL; the feeding ratio of glycidyl methacrylate to dimethyl sulfoxide is 0.39g:10mL.
[0053] With this setup, dimethyl sulfoxide can fully dissolve polyvinyl alcohol and glycidyl methacrylate, resulting in a homogeneous liquid phase environment and ensuring uniform distribution of the grafting reaction.
[0054] In some embodiments, the ratio of sodium hyaluronate to acidic solution is (1~2) g : (100~200 mL); the pH of the acidic solution is 4.7~4.8.
[0055] It can be noted that the acidic solution was prepared by slowly adding 1 mol / L hydrochloric acid solution dropwise to deionized water as the solvent, and the pH of the system was adjusted to 4.7~4.8 under stirring conditions.
[0056] In this embodiment, weak acidity is the optimal condition for activating the carboxyl groups of hyaluronic acid, avoiding degradation of the hyaluronic acid backbone, maintaining the molecular weight of the high-molecular-weight polymer, and ensuring the mechanical strength of the hydrogel subsequently prepared.
[0057] In one specific embodiment, the ratio of sodium hyaluronate to acidic solution is 1.5g:150mL; the pH of the acidic solution is 4.75.
[0058] With this setting, the ratio can effectively control the viscosity of the system, prevent uneven grafting reaction, and maintain the pH stability of the weak acid system.
[0059] In some embodiments, the molar ratio of N-hydroxysuccinimide, 1-ethyl-(3-dimethylaminopropyl)carbodiimide salt, and 3-aminophenylboronic acid is (4~5):(3.5~4.5):(4~5).
[0060] In this embodiment, 1-ethyl-(3-dimethylaminopropyl)carbodiimide salt is used as a carboxyl activator and N-hydroxysuccinimide is used as an activation intermediate stabilizer. Under weakly acidic conditions, the carboxyl groups of the side chain of sodium hyaluronate are activated. The activated carboxyl groups undergo an amidation condensation reaction with the primary amino group on the 3-aminophenylboronic acid molecule, and the phenylboronic acid group is grafted onto the hyaluronic acid macromolecule to prepare modified hyaluronic acid (HP). As a hydrogel matrix, it can be reversibly crosslinked with dynamic borate esters between phenylboronic acid and the hydroxyl groups of polyvinyl alcohol microspheres, giving the composite hydrogel self-healing ability and fixing the position of the microspheres, while improving the mechanical properties of the gel.
[0061] In one specific embodiment, the molar ratio of N-hydroxysuccinimide, 1-ethyl-(3-dimethylaminopropyl)carbodiimide salt, and 3-aminophenylboronic acid is 4.5:4:4.5.
[0062] With this setting, the molar ratio ensures the grafting efficiency of modified hyaluronic acid while reducing the excess residue of activating reagent, thus enabling the preparation of high-purity modified hyaluronic acid.
[0063] In some embodiments, the reaction temperature of the second grafting reaction is 25~35°C, the reaction time is 20~28h, and the dialysis time is 60~84h.
[0064] In this embodiment, the temperature and time range of the grafting reaction can reasonably improve the grafting efficiency and grafting uniformity of 3-aminophenylboronic acid, and the dialysis time range can maximize the purity of modified hyaluronic acid.
[0065] In one specific embodiment, the reaction temperature of the second grafting reaction is 30°C, the reaction time is 24 hours, and the dialysis time is 72 hours.
[0066] This setup ensures both the uniformity of grafting modification and the purity of the product, while also balancing operational efficiency and process stability.
[0067] In some embodiments, the mass ratio of methacrylated polyvinyl alcohol microspheres to modified hyaluronic acid is 1:(3.3~5).
[0068] In this embodiment, within this ratio range, the modified hyaluronic acid matrix can provide sufficient phenylboronic acid groups to form a large number of dynamic borate ester reversible covalent bonds with the ortho-hydroxyl groups on the surface of polyvinyl alcohol microspheres, constructing a continuous and complete cross-linked network. At the same time, the polymer matrix encapsulates and constrains the microspheres, effectively preventing the microspheres from slipping, agglomerating and migrating inside the gel.
[0069] In one specific embodiment, the mass ratio of methacrylated polyvinyl alcohol microspheres to modified hyaluronic acid is 1:3.75, that is, the amount of methacrylated polyvinyl alcohol microspheres is 0.08g and the amount of modified hyaluronic acid is 0.3g.
[0070] This configuration optimizes the gel's crosslinking density, mechanical strength, and self-healing properties, ensuring a uniform overall gel structure, stable performance, and improved reproducibility of the formulation system.
[0071] In some embodiments, the methacrylated polyvinyl alcohol microspheres are incubated in water for 10-14 hours, left to stand for 4-8 hours, and left to stand at a temperature of 3-5°C.
[0072] In this embodiment, sufficient incubation allows the methacrylated polyvinyl alcohol microspheres to restore their complete porous structure and expose hydroxyl sites, thereby improving the dynamic crosslinking efficiency and interfacial bonding strength between them and HP.
[0073] In one specific embodiment, the methacrylated polyvinyl alcohol microspheres were incubated in water for 12 hours, left to stand for 6 hours, and the standing temperature was 4°C.
[0074] This setup allows for slow and thorough improvement of the dynamic cross-linking network during low-temperature static setting, eliminating internal stress in the hydrogel and enhancing its mechanical stability and injectability.
[0075] Secondly, this application provides an injection-filled hydrogel based on polyvinyl alcohol microspheres, which is prepared using the preparation method of the injection-filled hydrogel based on polyvinyl alcohol microspheres in the first aspect.
[0076] The following are some specific embodiments. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0077] I. Preparation Method Example 1 This embodiment provides a method for preparing an injection-filled hydrogel based on polyvinyl alcohol microspheres, including the following steps; S1, 5g of polyvinyl alcohol was dissolved in 90mL of dimethyl sulfoxide and dissolved at 40℃ for 8h to obtain the first reaction solution. 0.11g of p-dimethylaminopyridine was added to the first reaction solution and dissolved for another 3h to obtain the second reaction solution. 0.39g of glycidyl methacrylate was mixed with 10mL of dimethyl sulfoxide and then added to the second reaction solution. After reacting for 30min, the temperature was raised to 60℃ to carry out the first grafting reaction. After 6h, the reaction was stopped. After the temperature dropped to room temperature, acetone was used for precipitation. After 2h, the mixture was washed three times with acetone and then vacuum dried to obtain methacrylated polyvinyl alcohol. S2, 1.5g of sodium hyaluronate was dissolved in 150mL of acidic solution with pH 4.75. After dissolving for 3h, 0.525g of N-hydroxysuccinimide was added. After 30min, 0.75g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide salt was added. After 1h, 0.75g of 3-aminophenylboronic acid was added. The second grafting reaction was carried out at 30℃. After reacting for 24h, the mixture was dialyzed with pure water for 72h and then lyophilized to obtain modified hyaluronic acid. S3, methacrylated polyvinyl alcohol was prepared into a 5% w / v solution. The solution was then used to prepare microspheres via microfluidic technology. The aqueous phase of the microfluidic process consisted of a 5% PG solution with 0.2% photoinitiator, namely lithium phenyl (2,4,6-trimethylbenzoyl)phosphate. The oil phase was prepared by dissolving 0.25g of Span-80 in 50ml of paraffin. The flow rate ratio of the aqueous phase to the oil phase was 7:30. The microspheres were fixed by UV irradiation, washed with carbon tetrachloride and water, and then freeze-dried to obtain methacrylated polyvinyl alcohol microspheres. S4. 0.08 g of lyophilized methacrylated polyvinyl alcohol microspheres were incubated in 5 mL of pure water (i.e., PGMCS mass volume fraction of 1.6% w / v) for 12 h. 0.3 g of lyophilized modified hyaluronic acid (i.e. HP mass volume fraction of 6% w / v) was added and dissolved for 5 h to form a gel. After standing at 4 °C for 6 h, the gel was drawn into a 1 mL syringe (26G needle, outer diameter 0.45 mm) and stored in a refrigerator at 4 °C.
[0078] Example 2 This embodiment provides a method for preparing an injection-filled hydrogel based on polyvinyl alcohol microspheres. The only difference from Example 1 is that 0.4 g glycidyl methacrylate is mixed with 10 mL of dimethyl sulfoxide, i.e., the molar ratio of p-dimethylaminopyridine to glycidyl methacrylate is 1:3.13. Other experimental parameters and conditions are basically the same as in Example 1, and will not be repeated here.
[0079] Example 3 This embodiment provides a method for preparing an injection-filled hydrogel based on polyvinyl alcohol microspheres. The only difference from Example 1 is that the methacrylated polyvinyl alcohol is prepared into a solution with a mass-volume fraction of 7.5% w / v. Other experimental parameters and conditions are basically the same as in Example 1, and will not be repeated here.
[0080] Example 4 This embodiment provides a method for preparing an injection-filled hydrogel based on polyvinyl alcohol microspheres. Compared with Example 1, the only difference is that the molar ratio of N-hydroxysuccinimide, 1-ethyl-(3-dimethylaminopropyl)carbodiimide salt, and 3-aminophenylboron is 5:4.5:5. Other experimental parameters and conditions are basically the same as in Example 1, and will not be repeated here.
[0081] Example 5 This embodiment provides a method for preparing an injection-filled hydrogel based on polyvinyl alcohol microspheres. The only difference from Example 1 is that the temperature of the second grafting reaction is 28°C. Other experimental parameters and conditions are basically the same as in Example 1, and will not be repeated here.
[0082] Example 6 This embodiment provides a method for preparing an injection-filled hydrogel based on polyvinyl alcohol microspheres. The only difference from Example 1 is that the mass ratio of methacrylated polyvinyl alcohol microspheres to modified sodium hyaluronate is 1:4. Other experimental parameters and conditions are basically the same as in Example 1, and will not be repeated here.
[0083] Comparative Example 1 This comparative example provides a method for preparing an injection-filled hydrogel based on polyvinyl alcohol microspheres. The only difference from Example 1 is that 0.35g of glycidyl methacrylate is mixed with 10mL of dimethyl sulfoxide, i.e., the molar ratio of p-dimethylaminopyridine to glycidyl methacrylate is 1:2.73. Other experimental parameters and conditions are basically the same as in Example 1, and will not be repeated here.
[0084] Comparative Example 2 This comparative example provides a method for preparing an injection-filled hydrogel based on polyvinyl alcohol microspheres. The only difference from Example 1 is that 0.55g of glycidyl methacrylate is mixed with 10mL of dimethyl sulfoxide, i.e., the molar ratio of p-dimethylaminopyridine to glycidyl methacrylate is 1:4.3. Other experimental parameters and conditions are basically the same as in Example 1, and will not be repeated here.
[0085] Comparative Example 3 This comparative example provides a method for preparing an injection-filled hydrogel based on polyvinyl alcohol microspheres. The only difference from Example 1 is that the mass ratio of methacrylated polyvinyl alcohol microspheres to modified sodium hyaluronate is 1:2. Other experimental parameters and conditions are basically the same as in Example 1, and will not be repeated here.
[0086] Comparative Example 4 This comparative example provides a method for preparing an injection-filled hydrogel based on polyvinyl alcohol microspheres. The only difference from Example 1 is that the mass ratio of methacrylated polyvinyl alcohol microspheres to modified sodium hyaluronate is 1:10. Other experimental parameters and conditions are basically the same as in Example 1, and will not be repeated here.
[0087] Comparative Example 5 This comparative example provides a method for preparing injection-filled hydrogels based on polyvinyl alcohol microspheres. The only difference from Example 1 is that the flow rate ratio of the aqueous phase to the oil phase in the microfluidic method is 1:2. Other experimental parameters and conditions are basically the same as in Example 1, and will not be repeated here.
[0088] Comparative Example 6 This comparative example provides a method for preparing injection-filled hydrogels based on polyvinyl alcohol microspheres. The only difference from Example 1 is that the flow rate ratio of the aqueous phase to the oil phase in the microfluidic method is 1:9. Other experimental parameters and conditions are basically the same as in Example 1, and will not be repeated here.
[0089] II. Testing Methods 1. The microstructure of the methacrylated polyvinyl alcohol microspheres prepared in Example 1 was tested using a Thermo Scientific Apreo 2S HiVac scanning electron microscope.
[0090] 2. The size of the methacrylated polyvinyl alcohol microspheres prepared in Example 1 was observed and statistically analyzed after incubation using an optical microscope (OLYMPUS) combined with microsphere size distribution statistics.
[0091] 3. The sodium hyaluronate and modified hyaluronic acid in Example 1 were subjected to proton nuclear magnetic resonance (NMR) spectrometry using a Bruker AVANCE NEO 400MHZ (Bruker GmbH, Switzerland) nuclear magnetic resonance spectrometer.
[0092] 4. The rheological properties of the injection-filled hydrogel prepared in Example 1 were tested using a Discovery HR 20 (TA, USA) rotational rheometer.
[0093] 5. The self-healing performance of the injection-filled hydrogel prepared in Example 1 was tested using an optical microscope (OLYMPUS).
[0094] 6. The injection extrusion force of the injection-filled hydrogel prepared in Example 1 was tested using a JHY-500M (Xiamen Jinheyuan Technology) universal material testing machine.
[0095] 7. The in vitro cell biocompatibility of the methacrylated polyvinyl alcohol microspheres and injection-filled hydrogels prepared in Example 1 was tested using the Cell Counting Kit 8 (CCK8) method combined with laser scanning confocal microscopy (CLSM).
[0096] 8. Using the Sprague-Dawley (SD) rat subcutaneous implantation model combined with histopathological section staining, the in vivo biocompatibility and subcutaneous implantation tissue reaction of the injectable filling hydrogel prepared in Example 1 were tested.
[0097] III. Test Result Analysis The microstructure of the methacrylated polyvinyl alcohol microspheres prepared in Example 1 was tested, and the results are as follows: Figure 2 As shown.
[0098] Depend on Figure 2 As can be seen, the freeze-dried polyvinyl methacrylate microspheres (PGMCS) are white solids. SEM testing shows that PGMCS exhibits a spherical structure with complete particle outlines and a rough, porous surface. This porous microstructure increases the specific surface area of the microspheres, facilitating subsequent dynamic cross-linking with HP. Figure 1 The synthetic reaction route shows that the phenylboronic acid groups on HP can fully contact the vicinal diol hydroxyl groups on the PGMCS side chains, achieving efficient cross-linking based on the dynamic covalent bonds of the borate ester, providing sufficient reaction contact surface and binding sites for the injectable hydrogel. Although the preparation conditions of PGMCS in Examples 2-3 were changed, they still have a spherical structure similar to that of PGMCS in Example 1. However, in Comparative Example 1, the amount of glycidyl methacrylate added was 0.35 g, at which point the microspheres could not undergo photocrosslinking and could not be formed. In Comparative Example 2, the amount of glycidyl methacrylate added was 0.55 g, and the PGMCS prepared in this way had an excessively large particle size and inconsistent, non-spherical shape.
[0099] The size of the methacrylated polyvinyl alcohol microspheres prepared in Example 1 was observed and statistically analyzed after incubation. The results are as follows: Figure 3 As shown.
[0100] Depend on Figure 3It can be seen that most PGMCS exhibit a complete spherical outline and good particle dispersion, indicating good morphological uniformity of the prepared PGMCS. The particle size distribution histogram and fitted normal distribution curve show that the microsphere particle size is concentrated in the 140~220μm range, with the peak particle size mainly around 190~200μm. The particle size distribution curve shows an approximately normal distribution with a narrow distribution, ensuring a uniform interface when the microspheres are combined with HA-PBA. In Comparative Example 5, the methacrylated polyvinyl alcohol microspheres prepared had excessively large particle sizes due to insufficient shear force in the oil phase, making the hydrogel prepared after combining with HP prone to clogging the needle. In Comparative Example 6, the methacrylated polyvinyl alcohol microspheres had excessively small particle sizes, resulting in insufficient long-term support and poor injection filling effect in the hydrogel prepared after combining with HP.
[0101] The sodium hyaluronate and modified hyaluronic acid in Example 1 were subjected to 1H NMR spectroscopy, and the results are as follows: Figure 4 As shown.
[0102] Depend on Figure 4 It can be seen that sodium hyaluronate (HA) molecules do not have a benzene ring structure and have no characteristic peak at a chemical shift of 7-8 ppm. Modified hyaluronic acid (HP) grafted with 3-aminophenylboronic acid shows a characteristic proton peak of the benzene ring at a chemical shift of 7-8 ppm, proving that the phenylboronic acid group has been successfully grafted onto the hyaluronic acid macromolecular chain.
[0103] The rheological properties of the injection-filled hydrogel prepared in Example 1 were tested, and the results are as follows: Figure 5 As shown.
[0104] Depend on Figure 5 It can be seen that during multiple cycles of alternating strain failure and static repair, the storage modulus G' of the hydrogel can rapidly recover after structural damage and remains higher than the loss modulus G'', indicating that the injection-filled hydrogel prepared based on the dynamic reversible covalent bonds of borate esters possesses efficient and repeatable self-healing capabilities. Simultaneously, this injection-filled hydrogel exhibits significant shear-thinning behavior; as the shear rate increases, the apparent viscosity of the system continuously decreases, confirming that the injection-filled hydrogel possesses good injectability. Under external force, it can be smoothly injected through a needle and recovers its gel state after being removed from the shear environment. Comparative Examples 3-4, by adjusting the mass ratio of PGMCS to HP from 1:3.75 to 1:2 and 1:10 respectively, deviated from the optimal crosslinking ratio. Adding less HP and less PGMCS both reduced the effective crosslinking sites during the crosslinking process, decreased the crosslinking density, lowered the modulus of the resulting injection-filled hydrogel, and caused the hydrogel to soften and lose viscoelasticity.
[0105] The self-healing properties of the injection-filled hydrogel prepared in Example 1 were tested, and the results are as follows: Figure 6 As shown.
[0106] Depend on Figure 6 As can be seen, after the cross-sections of two differently colored hydrogels adhered to each other, they fused together autonomously, achieving macroscopic morphological repair. This indicates that the injectable filler hydrogel possesses self-healing capabilities. Microscopic morphological observation shows that the two phases at the healing interface are interpenetrating and interwoven without clear separating gaps, indicating good interfacial bonding. This suggests that the dynamic reversible cross-linked network inside the hydrogel can be reconstructed at the cross-section, achieving interface repair. The injectable filler hydrogels prepared in Examples 2-6 also exhibit good self-healing properties, achieving tissue repair after injection.
[0107] The injection-filled hydrogel prepared in Example 1 was subjected to an in vitro injection extrusion force test, and the results are as follows: Figure 7 As shown.
[0108] Depend on Figure 7 It can be seen that 0.45mm (26G) and 0.70mm (22G) are two injection needles with different outer diameters. Within 0~5s, the extrusion force of both needles rises rapidly and then enters a steady-state extrusion force plateau. This indicates that the injection-filled hydrogel has a rapid injection response and excellent creep stability under continuous shearing.
[0109] The methacrylated polyvinyl alcohol microspheres and injection-filled hydrogel prepared in Example 1 were subjected to in vitro cell (HUVEC) biocompatibility tests, and the results are as follows: Figure 8 As shown.
[0110] Depend on Figure 8 As can be seen, the fluorescence qualitative analysis showed a large number of green fluorescent dots, indicating that the cells survived in large numbers and were well dispersed in the hydrogel system. On the first day of culture, neither PGMCS nor the composite hydrogel material was cytotoxic, and the cell survival rate was similar to that of the blank control group. On the third day of culture, both PGMCS and the composite hydrogel significantly promoted cell proliferation, proving that PGMCS and the composite hydrogel had good in vitro biocompatibility.
[0111] The results of hematoxylin-eosin (HE) staining for subcutaneous implantation tissue reaction testing of the injectable filler hydrogel prepared in Example 1 are as follows: Figure 9 As shown.
[0112] Depend on Figure 9 It can be seen that after subcutaneous injection of hydrogel into SD rats ( Figure 9 In (c, d), the hydrogel implant occupies the subcutaneous soft tissue in a clump-like in situ, with a uniform overall distribution and a clear boundary between the implant and the surrounding tissue. Numerous blue cell nuclei appear between the microspheres, whereas after injection of saline... Figure 9 In (a, b), no new large number of cell nuclei were observed.
[0113] Masson staining results for subcutaneous implantation tissue reaction testing of the injectable filler hydrogel prepared in Example 1 are as follows: Figure 10 As shown.
[0114] Depend on Figure 10 It can be seen that, compared to injecting saline solution ( Figure 10 e, f), injecting hydrogel ( Figure 10 After g and h), the collagen distribution near the microspheres was significantly increased and the coloring was darker. Collagen proliferation also existed in the interstices between the microspheres. No excessively thickened dense fibrous capsule was observed in the implantation area. The newly formed collagen grew uniformly along the interstices between the microspheres, and the material and the host tissue achieved good integration. This confirms that the injectable filler hydrogel has excellent in vivo biocompatibility and can effectively promote collagen regeneration.
[0115] Sirius red staining results for subcutaneous implantation tissue reaction testing of the injectable filler hydrogel prepared in Example 1 are as follows: Figure 11 As shown.
[0116] Depend on Figure 11 It can be seen that on days 3 and 7 after hydrogel injection, the implanted area is dominated by bright yellow, coarse fiber bundles, with type I collagen being the most abundant at this time. On day 15 after hydrogel injection, a large number of green, fine, reticular type III collagen fibers can be seen in the sample, which are mature collagen. The above results indicate that the injected filling hydrogel can continuously induce collagen regeneration. As the implantation time is prolonged, the newly formed collagen can undergo orderly remodeling, and the collagen composition is gradually adjusted to form structurally stable new soft tissue.
[0117] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing embodiments by combining some of the constituent elements, are also included in the scope of this application without departing from the spirit of this application.
[0118] Furthermore, although this application has been described with reference to preferred embodiments, various modifications can be made thereto and components can be replaced with equivalents without departing from the scope of this application. In particular, the technical features mentioned in the various embodiments can be combined in any manner, provided there is no structural conflict. This application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. A method for preparing an injection-filled hydrogel based on polyvinyl alcohol microspheres, characterized in that, Includes the following steps: Polyvinyl alcohol is dissolved in a solvent to obtain a first reaction solution. p-Dimethylaminopyridine is added to the first reaction solution and dissolved to obtain a second reaction solution. Glycidyl methacrylate is mixed with the solvent and then added to the second reaction solution to carry out a first grafting reaction. After the reaction is complete, the product is precipitated, washed, and dried to obtain methacrylated polyvinyl alcohol. The molar ratio of polyvinyl alcohol, p-dimethylaminopyridine, and glycidyl methacrylate is (100~150):1:(2.9~3.9). Sodium hyaluronate was dissolved in an acidic solution, and then N-hydroxysuccinimide, 1-ethyl-(3-dimethylaminopropyl)carbodiimide salt, and 3-aminophenylboronic acid were added sequentially to carry out a second grafting reaction. After the reaction was completed, modified hyaluronic acid was obtained by dialysis and lyophilization. The ratio of sodium hyaluronate to the acidic solution was (1~2) g: (100~200) mL. The molar ratio of N-hydroxysuccinimide, 1-ethyl-(3-dimethylaminopropyl)carbodiimide salt, and 3-aminophenylboronic acid was (4~5): (3.5~4.5): (4~5). The methacrylated polyvinyl alcohol was prepared into a solution with a mass-volume fraction of 4%~7.5% w / v, and the solution was then used to prepare microspheres by microfluidic technology. After fixation, washing, and freeze-drying, methacrylated polyvinyl alcohol microspheres were obtained. The flow rate ratio of the aqueous phase to the oil phase in the microfluidic method was 1:(3~7.5). The methacrylated polyvinyl alcohol microspheres were then combined with the modified hyaluronic acid at a mass ratio of 1:(3.3~5) to obtain an injection-filled hydrogel.
2. The method for preparing an injection-filled hydrogel based on polyvinyl alcohol microspheres according to claim 1, characterized in that, The step of combining the methacrylated polyvinyl alcohol microspheres with the modified hyaluronic acid includes: After incubating the methacrylated polyvinyl alcohol microspheres in water, the modified hyaluronic acid was added to dissolve them and a gel was obtained. After standing, aspirating into a syringe, and refrigerating, an injection-filled hydrogel was obtained. The particle size of the methacrylated polyvinyl alcohol microspheres after incubation in water is 140~220μm.
3. The method for preparing an injection-filled hydrogel based on polyvinyl alcohol microspheres according to claim 1, characterized in that, The reaction temperature of the first grafting reaction is 50~70℃, and the reaction time is 5~8h.
4. The method for preparing an injection-filled hydrogel based on polyvinyl alcohol microspheres according to claim 1, characterized in that, The solvent is dimethyl sulfoxide; When the polyvinyl alcohol is dissolved in the solvent, the feeding ratio of the polyvinyl alcohol to the dimethyl sulfoxide is (4~6) g: (80~100) mL; When the glycidyl methacrylate is mixed with the solvent, the feeding ratio of the glycidyl methacrylate to the dimethyl sulfoxide is (0.3~0.5) g: (8~12) mL.
5. The method for preparing an injection-filled hydrogel based on polyvinyl alcohol microspheres according to claim 1, characterized in that, The pH of the acidic solution is 4.7 to 4.
8.
6. The method for preparing an injection-filled hydrogel based on polyvinyl alcohol microspheres according to claim 1, characterized in that, The reaction temperature of the second grafting reaction is 25~35℃, the reaction time is 20~28h, and the dialysis time is 60~84h.
7. The method for preparing an injection-filled hydrogel based on polyvinyl alcohol microspheres according to claim 2, characterized in that, The methacrylated polyvinyl alcohol microspheres are incubated in water for 10-14 hours, and the settling time is 4-8 hours, with a settling temperature of 3-5°C.
8. An injection-filled hydrogel based on polyvinyl alcohol microspheres, characterized in that, It is prepared by the method for preparing an injection-filled hydrogel based on polyvinyl alcohol microspheres as described in any one of claims 1-7.